Leaders in making - "Singh, U. B." (Delhi, 2007)
Preface Contributors Contextualising Political Leadership in India Urban Politics: Emerging Leadership in Women Representative Dimension of Municipal Political Leadership-Emerging Scene in South India Local Leadership as a Representative Nationa
Keywords: Leadership